2015
DOI: 10.1007/s10878-015-9932-4
|View full text |Cite
|
Sign up to set email alerts
|

On the kidney exchange problem: cardinality constrained cycle and chain problems on directed graphs: a survey of integer programming approaches

Abstract: The Kidney Exchange Problem (KEP) is a combinatorial optimization problem and has attracted the attention from the community of integer programming/combinatorial optimisation in the past few years. Defined on a directed graph, the KEP has two variations: one concerns cycles only, and the other, cycles as well as chains on the same graph. We call the former a Cardinality Constrained Multi-cycle Problem (CCMcP) and the latter a Cardinality Constrained Cycles and Chains Problem (CCCCP). The cardinality for cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The EE-MTZ model [Mak-Hau 2015], another compact formulation, uses the variables and constraints of the extended edge formulation to model cycles and a variant of the Miller-Tucker-Zemlin model for the traveling salesman problem to model chains. The same paper introduces the exponentially-sized SPLIT-MTZ model, which adds redundant constraints to the edge formulation in order to tighten the LP relaxation.…”
Section: Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The EE-MTZ model [Mak-Hau 2015], another compact formulation, uses the variables and constraints of the extended edge formulation to model cycles and a variant of the Miller-Tucker-Zemlin model for the traveling salesman problem to model chains. The same paper introduces the exponentially-sized SPLIT-MTZ model, which adds redundant constraints to the edge formulation in order to tighten the LP relaxation.…”
Section: Prior Researchmentioning
confidence: 99%
“…The pricing problem is to bring at least one new positive price cycle into the model, or prove that none exist. Multiple methods exist for solving the pricing problem in kidney exchange [Abraham et al 2007;Glorie et al 2014;Mak-Hau 2015;Plaut et al 2016a]; in our experimental section, we use the cycle pricer of Glorie et al [2014] with the bugfix of Plaut et al [2016a].…”
Section: Practical Implementation Of the Picef Modelmentioning
confidence: 99%
“…Limitations on the maximum length of cycles may be weakened in the future. It is reported that a 9-cycle exchange was performed successfully in 2015 [20]. In this section, we discuss the KEP with L ≥ 3 parameterized by the size of kidney transplants.…”
Section: A Randomized Algorithm Based On Algebraic Techniquementioning
confidence: 99%
“…Mak-Hau [19] studied the edge formulations for the KEP with and without chains and presented some polyhedral results. For a detailed review of various IP approaches to solving the KEP, see a recent survey of Mak-Hau [20].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we will present arc-based integer programming models of the Cardinality Constrained Multicycle Problem (CCMcP) and the Cardinality Constrained Cycles and Chains Problem (CCCCP) and study their polyhedral structures, in the hope of finding strong constraints to be applied in a branch-and-bound framework for finding exact solutions in computationally efficient ways. Preliminary results of the exponential-size arc based formulations for the CCMcP and the CCCCP are presented in a companion paper Mak-Hau (2015a).…”
Section: Introductionmentioning
confidence: 99%